Analysis of Fermi-LAT observations, UHECRs and neutrinos from the radio galaxy Centaurus B - Fraija Cabrera, Nissim Illich (2019)
Centaurus B (Cen B) is one of the closest and brightest radio-loud galaxy in the southern sky. This radio galaxy, proposed as a plausible candidate for accelerating ultra-high-energy cosmic rays (UHECRs), is near the highest-energy neutrino event reported (IC35) in the High-Energy Starting Events catalog. Pierre Auger observatory reported the highest energy comic rays during 10 years of collecting data with some of them around this source. In this paper, the analysis of the gamma-ray spectrum and the light curve above 200 MeV is presented with nine years of cumulative Fermi-LAT data around Cen B . Taking into consideration the multi-wavelength observations carried out about this radio galaxy, leptonic and hadronic scenarios are introduced in order to fit the spectral energy distribution, assuming that the gamma-ray flux is produced in a region close to the core and in the extended lobes. Using the best-fit values found, several physics properties of this radio galaxy are derived. Furthermore, a statistical analysis of the cosmic ray distribution around Cen B is performed, finding that this distribution is not different from the background at a level of significance of 5%. Considering the UHECR event associated to this source by Moskalenko et al. [1] and extrapolating its luminosity to low energies, we do not find enough evidence to associate the highest-energy neutrino event (IC35) with this radio galaxy.